Central Lines in Children - Rishi Agrawal; Neha Shah (Association of American Medical Colleges, 2015)
Abstract Introduction Children with special health care needs are increasingly prevalent in U.S. hospitals. The pediatric hospitalist is often the primary provider of inpatient care for these patients. However, exposure to this patient population during training varies from provider to provider. No published educational curricula are specific to the inpatient care of this population. The purpose of this project was to build a multimodal educational curriculum for providers with the overall goal of improving inpatient care for this at-risk population. This part of the curriculum focuses on the use of central lines in children. Others in the curriculum address dysautonomia, spasticity, enteric feeding tubes, gastroesophageal reflux disease in the neurologically impaired child, ventriculoperitoneal shunts, and autonomic dysreflexia and palliative care. Methods This resource is a self-directed education module on central lines in children, including indications for placement, types of lines available, and prevention and treatment of complications. It is primarily composed of topic-specific multimedia learning sections and contains PowerPoint slide shows, questions for assessment, and an instructor's guide. Results This central line module has been piloted among pediatric hospitalists in two institutions, with effectiveness measured by pre− and posttest surveys. Complete sets of pre− and posttest data were collected from four learners. The average pretest score was 65.0%, and the average posttest score was 92.5%. Discussion This resource was created to provide pediatricians with educational materials related to care of the medically complex child with a central line. However, this module covers only the most commonly used central lines in children and should not be considered a comprehensive review of all available central lines. Furthermore, in an effort to provide focus and offer useful tips for management of lines, the module concentrates on the practical aspects of choosing and maintaining central lines, as this is an area not consistently taught to general pediatric inpatient providers; the module does not discuss the conditions that commonly require children to have central lines.